Working from home, hours worked and wages: heterogeneity by gender and parenthood - Arntz, Melanie; Ben Yahmed, Sarra; Berlingieri, Francesco (Labour economics, 2022)
Working from home (WfH) has been widely adopted since the Covid-19 pandemic. Pre-pandemic evidence on how hybrid work arrangements relate to labour market outcomes is a scarce and valuable benchmark. We exploit the German Socio-Economic Panel between 1997 and 2014 to investigate how such a work arrangement relates to working hours, wages and job satisfaction for different demographic groups. We find that childless employees work an extra hour of unpaid overtime per week and report higher job satisfaction after taking up WfH. Among parents, gender differences in working hours and monthly earnings are lower after WfH take-up. However, hourly wage increases with WfH take-up are limited to fathers, unless mothers change employers. We discuss the role of career changes, commuting and working-time flexibility in explaining these findings.